Naïve, unenculturated chimpanzees fail to make and use flaked stone tools - Bandini, Elisa (Open Res Eur, 2021)
Background: Despite substantial research on early hominin lithic technologies, the learning mechanisms underlying flake manufacture and use are contested. To draw phylogenetic inferences on the potential cognitive processes underlying the acquisition of both of these abilities in early hominins, we investigated if and how one of our closest living relatives, chimpanzees ( Pan troglodytes), could learn to make and use flakes. Methods: Across several experimental conditions, we tested eleven task-naïve chimpanzees (unenculturated n=8, unknown status n=3) from two independent populations for their abilities to spontaneously make and subsequently use flakes as well as to use flakes made by a human experimenter. Results: Despite the fact that the chimpanzees seemed to understand the requirements of the task, were sufficiently motivated and had ample opportunities to develop the target behaviours, none of the chimpanzees tested made or used flakes in any of the experimental conditions. Conclusions: These results differ from all previous ape flaking experiments, which found flake manufacture and use in bonobos and one orangutan. However, these earlier studies tested human-enculturated apes and provided test subjects with flake making and using demonstrations. The contrast between these earlier positive findings and our negative findings (despite using a much larger sample size) suggests that enculturation and/or demonstrations may be necessary for chimpanzees to acquire these abilities. The data obtained in this study are consistent with the hypothesis that flake manufacture and use might have evolved in the hominin lineage after the split between Homo and Pan 7 million years ago, a scenario further supported by the initial lack of flaked stone tools in the archaeological record after this split. We discuss possible evolutionary scenarios for flake manufacture and use in both non-hominin and hominin lineages.